8th GCC: Consolidated feedback to US FDA on the 2013 Draft FDA Guidance on Bioanalytical Method Validation. (November 2014) - Bower, Joseph; Fast, Douglas; Garofolo, Fabio; Gouty, Dominique; Hayes, Roger; Lowes, Steve; Nicholson, Robert; LeLacheur, Richard; Bravo, Jennifer; Shoup, Ronald; Dumont, Isabelle; Carbone, Mary; et al.
The 8 th GCC Closed Forum for Bioanalysis was held in Baltimore, MD, USA on 5 December 2013, immediately following the 2013 AAPS Workshop (Crystal City V): Quantitative Bioanalytical Methods Validation and Implementation – The 2013 Revised FDA Guidance . This GCC meeting was organized to discuss the contents of the draft revised FDA Guidance on bioanalytical method validation that was published in September 2013 and consolidate the feedback of the GCC members. In attendance were 63 senior-level participants, from seven countries, representing 46 bioanalytical CRO companies/sites. This event represented a unique opportunity for CRO bioanalytical experts to share their opinions and concerns regarding the draft FDA Guidance, and to build unified comments to be provided to the FDA.